2017
DOI: 10.1007/s10103-017-2156-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial LED therapy on amyloid-β toxin 25–35 in the hippocampal region of rats

Abstract: Excessive Aβ deposition in the brain is associated with the formation of senile plaques, and their diffuse distribution is related to Alzheimer's disease. Thirty rats (EG) were irradiated with light-emitting diode (photobiomodulation (PBM)) in the frontal region of the skull after being inoculated with the Aβ toxin in the hippocampus; 30 rats were used as the control group (CG). The analysis was conducted at 7, 14, and 21 days after irradiation. We observed a decreased in Aβ deposits in treated animals compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…da Luz Eltchechem et al [147] also used rats but injected the hippocampus with Aβ25-35 peptide and treated them daily with 627 nm laser for 100 s, 7 J/cm 2 for 21 days. The use of tPBM significantly reduced the Aβ plaques, and improved spatial memory and behavioral and motor skills in treated animals on day 21.…”
Section: Tpbm For Ad In Animal Modelsmentioning
confidence: 99%
“…da Luz Eltchechem et al [147] also used rats but injected the hippocampus with Aβ25-35 peptide and treated them daily with 627 nm laser for 100 s, 7 J/cm 2 for 21 days. The use of tPBM significantly reduced the Aβ plaques, and improved spatial memory and behavioral and motor skills in treated animals on day 21.…”
Section: Tpbm For Ad In Animal Modelsmentioning
confidence: 99%
“…The power to the skin surface was 92 mM, and the power density was 117.2 mW/cm 2 ( Figure S1a). The PBM system was stationary positioned in skin contact at the frontal region in the head of mice; the irradiation was applied once a day for 10 min, at the irradiation dose of 6 J/cm 2 with power of 8.75 mW exposure to the cortex for 30 days (without local temperature increase in the scalp and brain tissue) (Luz Eltchechem et al, 2017). Refer to our previous studies on the transmittance of PBM from the upper part of the exposed brain to the interior of the hippocampus, the transmittance was approximately 30% (Zhang et al, 2020), and then, the hippocampus is required to obtain a dose of 2 J/cm 2 , which indicated that 6 J/cm 2 PBM irradiation is needed.…”
Section: Pbm Treatmentmentioning
confidence: 99%
“…PBM may protect against the neuronal death and mitochondrial dysfunction associated with Alzheimer's disease, which is why this novel treatment has such broad potential (Table 1). In transgenic animal models associated with β-amyloid or tau, PBM reduces cognitive deficits, β-amyloid plaques, tau-associated neurofibrillary tangles, and oxidative stress while increasing the production of adenosine [31][32][33][34][35][36]. Additionally, in vitro studies have shown that PBM decreases β-amyloid plaques while increasing cell survival and ATP production [37].…”
Section: Alzheimer's Disease and Pbmmentioning
confidence: 99%